2023
DOI: 10.1164/rccm.202210-1846st
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward Equitable Care for Sleep Apnea in the United States: Positive Airway Pressure Adherence Thresholds: An Official American Thoracic Society Policy Statement

Abstract: Background Positive airway pressure (PAP) is a highly effective treatment for obstructive sleep apnea (OSA), but adherence limits its efficacy. In addition, coverage of PAP by CMS (Centers for Medicare & Medicaid Services) and other insurers in the United States depends on adherence. This leaves many beneficiaries without PAP, disproportionally impacting non-white and low socioeconomic position patients with OSA and exacerbating sleep health disparities. Methods An inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Yet, our results demonstrate that those with low-income subsidy and dual Medicare/Medicaid eligibility have greater benefit of PAP against MACE. These results highlight opportunities to implement care programs designed to minimize health disparities, as recently proposed 75 . Our study also identified stronger effects of PAP initiation among those with comorbid conditions, particularly obesity and atrial fibrillation (for both mortality and MACE), as well as COPD, type 2 diabetes, and those with more comorbidities according to the CCI.…”
Section: Discussionmentioning
confidence: 55%
“…Yet, our results demonstrate that those with low-income subsidy and dual Medicare/Medicaid eligibility have greater benefit of PAP against MACE. These results highlight opportunities to implement care programs designed to minimize health disparities, as recently proposed 75 . Our study also identified stronger effects of PAP initiation among those with comorbid conditions, particularly obesity and atrial fibrillation (for both mortality and MACE), as well as COPD, type 2 diabetes, and those with more comorbidities according to the CCI.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to different coverage policies, different patient populations can also impact performance of PAP adherence algorithms. Because adherence can impact access to care, this is an especially important consideration from a health equity perspective, 25 particularly because improvement in some outcomes may be seen with lower levels of PAP use. 26 For example, studies have demonstrated an association between lower socioeconomic status and reduced PAP adherence.…”
Section: Discussionmentioning
confidence: 99%
“…OSA health literacy has been found to be lower in individuals with lower educational attainment and socioeconomic status ( 36 ). Socioeconomic disparities were acknowledged as contributing to sleep health disparities and CPAP adherence in a recent American Thoracic Society consensus document ( 37 ).…”
Section: Introductionmentioning
confidence: 99%